Coal pulverization by electric pulse method for water-coal fuel - Nussupbekov, B.R.; Khassenov, A.K.; Karabekova, D.Zh.; Nussupbekov, U.B.; Stoev, M.; Bolatbekova, M.M. (KSU publ., 2019)
In the article describes the electrohydraulic method as a source of high energy concentration for the disintegration of the components of water-coal fuel in an aqueous medium under the action of pulsed discharges. The proposed method of grinding coal is based on the use of pulsed shock wave energy resulting from a spark electric discharge in a liquid. The essence and distinctive feature of the proposed technology is that the processing of the material using the energy of the shock wave released with electrohydraulic action allows to obtain a quickly crushed product of a given size. The degree of grinding of the material on the dependence of the electrical and geometric parameters of the installation is determined. The optimal parameters of the capacitance of capacitor banks, voltage of pulse discharges, number of pulse discharges and forming gap distance are proposed. The presented results of laboratory tests at different temperature mode, which proves that the grinding of coal by electric discharge method does not require additional cooling, since the processing process is carried out in a liquid medium. The main working element in the electric pulse processing is a spark discharge, the resulting product is not contaminated with the materials of grinding bodies, characteristic of the traditional mechanical method.
Keywords: coal; grinding; spark discharge; discharge voltage; electric pulse method